2008
DOI: 10.1530/eje-07-0595
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is negatively associated with the presence of thyroglobulin autoantibody and to a lesser degree with thyroid peroxidase autoantibody in serum: a population study

Abstract: Background: Autoimmune thyroid diseases are common and the prevalence of circulating thyroid antibodies (thyroid peroxidase antibody, TPO-Ab and thyroglobulin antibody, Tg-Ab) is high in the population. The knowledge of a possible association between lifestyle factors and circulating thyroid antibodies is limited. Aim: To evaluate the correlation between smoking habits and the presence of circulating TPO-Ab and Tg-Ab. Material and methods: In a cross-sectional comparative population study performed in two area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 38 publications
5
44
1
1
Order By: Relevance
“…5 A significant negative association was observed between smoking and the presence of TPOAb and TgAb. 38 Furthermore, a prospective study reported that smoking cessation might increase the risk of TPOAb and TgAb positivity. 39 Similarly, the current study demonstrated that the prevalence of TPOAb and/or TgAb positivity was lower in smokers (occasional and frequent) than in nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…5 A significant negative association was observed between smoking and the presence of TPOAb and TgAb. 38 Furthermore, a prospective study reported that smoking cessation might increase the risk of TPOAb and TgAb positivity. 39 Similarly, the current study demonstrated that the prevalence of TPOAb and/or TgAb positivity was lower in smokers (occasional and frequent) than in nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for having thyroid Abs was similar in moderate and heavy smokers. Comparison between former and never smokers also did not reveal any difference in the risk of having thyroid Abs [14]. But Cho et al failed to establish an association between smoking status and the level of TPO-Abs [5].…”
Section: Influence Of Cigarette Smoking On Thyroperoxidase Antibodiesmentioning
confidence: 94%
“…Several studies have shown cigarette smoking to be associated with increased serum Tg (Bertelsen and Hegedus, 1994;Cahoon et al, 2013;Knudsen et al, 2002;Krejbjerg et al, 2016), and with significant changes to indicators of thyroid dysfunction (including decreased serum TSH, increased thyroid size, and increased risk of prevalent non-toxic goiter and thyroid nodules in iodine deficient areas) Pedersen et al, 2008;Wiersinga, 2013). Increases in serum Tg among smokers have been attributed to thiocyanate-a metabolite of the cigarette smoke component, cyanide, and a competitive inhibitor of thyroidal iodine uptake (Tonacchera et al, 2004).…”
Section: Demographic Factors Thyroid Function and 131 I Thyroid Dosementioning
confidence: 99%